Arsenal of technique, resultativity and effectiveness of judokas at world championships - Pimenovs, E.; Pimenovs, A.; Rebrovs, A. (LASE Journal of Sport Science, 2020)
The evaluation of technical mastery of judokas and its differences in high-class athletes performing in competitions have been relatively little studied. The research aim is to study the arsenal of technique, resultativity and effectiveness of high-class judokas in the 2005 and 2014 World Championships in the weight category up to 90 kilograms. The research of the technical arsenal used in the competition helps to determine the level of technical readiness, as well as permits to compare and determine the direction and development trends of technical mastery. This information will be used by judo professionals to adjust high-level judo training international competitions. In this work we study the arsenal of technique, resultativity and effectiveness of high-class judokas in the 2005 and 2014 World Championships in the weight category up to 90 kilograms. The study included literature research, an analysis of competition documents and protocols, as well as an analysis of competition videos from the 2005 and 2014 World Championships, which analysed 32 high-class athletes (award- winners). Methods of mathematical statistics. In the 2005 World Championship for men in the weight category up to 90kg, 12 resultative throws were registered, of which 6 (50%) were from the leg technique, 4 (34%) with falling on the back or on the side, 1 (8%) hand technique and 1 (8%) shoulder technique, 0 from the hip technique. In turn, in the 2014 World Championship, 58 resultative throws were observed, of which 29% were hip technique, 24% - leg technique, 23% - shoulder technique, 19% - sacrifice throws, 5% - hand technique. Resultativity (R) is the average mark of a judoka`s offensive actions, it determines the quality of the offensive actions. The highest R at the 2005 World Championship is 5.1 points in the weight category up to 90kg, while in 2014 - 4.1 points. The effectiveness indicator (E) of offensive actions is the number of assessed offensive actions divided by the total number of offensive actions. At the 2005 World Championship, the average E indicator for - 90kg is 67%, while in 2014 - 57%.